A synthetic curcuminoid analogue, 2,6-Bis-4-(Hydroxyl-3-Methoxybenzylidine)-Cyclohexanone (BHMC) ameliorates acute airway inflammation of allergic asthma in ovalbumin-sensitized mice - Tham, Chau Ling; Sin, Yee Yeoh; Ong, Chun Hao; Harith, Hanis Hazeera; Israf Ali, Daud Ahmad (Hindawi Publishing Corporation, 2021)
2,6-Bis-(4-hydroxyl-3-methoxybenzylidine) cyclohexanone (BHMC), a synthetic curcuminoid analogue, has been shown to exhibit anti-inflammatory properties in cellular models of inflammation and improve the survival of mice from lethal sepsis. We further evaluated the therapeutic effect of BHMC on acute airway inflammation in a mouse model of allergic asthma. Mice were sensitized and challenged with ovalbumin (OVA), followed by intraperitoneal administration of 0.1, 1, and 10 mg/kg of BHMC. Bronchoalveolar lavage fluid, blood, and lung samples were collected, and the respiratory function was measured. OVA sensitization and challenge increased airway hyperresponsiveness (AHR) and pulmonary inflammation. All three doses of BHMC (0.1-10 mg/kg) significantly reduced the number of eosinophils, lymphocytes, macrophages, and neutrophils, as well as the levels of Th2 cytokines (IL-4, IL-5 and IL-13) in bronchoalveolar lavage fluid (BALF) as compared to OVA-challenged mice. However, serum level of IgE was not affected. All three doses of BHMC (0.1-10 mg/kg) were effective in suppressing the infiltration of inflammatory cells at the peribronchial and perivascular regions, with the greatest effect observed at 1 mg/kg which was comparable to dexamethasone. Goblet cell hyperplasia was inhibited by 1 and 10 mg/kg of BHMC, while the lowest dose (0.1 mg/kg) had no significant inhibitory effect. These findings demonstrate that BHMC, a synthetic nonsteroidal small molecule, ameliorates acute airway inflammation associated with allergic asthma, primarily by suppressing the release of inflammatory mediators and goblet cell hyperplasia to a lesser extent in acute airway inflammation of allergic asthma.